Factors Influencing the Low Enrolment of King Abdulaziz University Engineering Students in Nuclear Engineering: Fears and Assurances - , K. K. Oraby.; , S. S. Mahmoud; , N. A. Al-Enezi (Archives of Current Research International, 2025)
The continuous increase in Co2 emissions in the atmosphere calls for instant response to find better alternatives for fossil fuels. Nuclear energy as carbon free energy might be one of the best alternatives. Unfortunately, some of King Abdelaziz University (KAU) students are unwilling to join nuclear engineering for different reasons. Aim: This study is of great importance as it is meant to motivate KAU students to enroll in nuclear engineering NE as the most promising field. The Kingdom of Saudi Arabia is heading towards decarbonated industry and signed global agreements with this regard. Sample: The sample of the study was prep. year engineering students at King Abdulaziz university in 2024/25. Methodology: To conduct this study, the researchers used quantitative and qualitative research procedures. They designed a questionnaire to inform students about the importance of NE and to investigate the reasons behind students’ reluctance to join NE; in addition to finding ways to motivate and convince KAU students that NE is one of the best choices currently. In order to know the reasons for students’ reluctance from the instructors’ perspective, the researchers interviewed three PhD holders in NE from the NE department at KAU. Results: The findings of the study detected lack of awareness among the students with regard to the importance of NE. This was apparent in the bar charts where “I don’t know” bars are almost similar to “Agree”. It was also clear that students still have the traditional image that nuclear power is only associated with devastation and those who deal with this field will end up either handicapped or having permanent disability. Conclusion: The study recommended that schools, universities, and other related institutions should spread the awareness that nuclear energy is safe to deal with, job promising, and it is the future for low or zero emissions.